The Importance Of Student Health Record Books In School To Realize Children’s Health - M., Soenarnatalina; Sulistyorini, Yuly; Mahmudah, Mahmudah; Indriani, Diah (Opción, 2019)
Health services in schools are carried out through collaboration between Com- munity Health Centers (Puskesmas) and School Health Programs (UKS). It is necessary to learn about schools and their readiness in making student health record books for elementary school (SD) students. The aim of the research was to identify the readiness of schools implementing student health records pro- grams. This research was conducted in 3 elementary schools, namely 2 public schools and 1 private school in Surabaya City, with 8 informants. The results of in-depth interviews showed that UKS activities have been carried out in all schools at the elementary school level but have not been optimal. Student health record books that support student health status do not yet exist in all schools. The absence of students at school has not been followed up if the stu- dents do not attend because of illness.